Threonine to lysine ratio in diets of tambaqui juveniles (Colossoma macropomum) - Firmo, Danielli dos Santos; Bomfim, Marcos Antonio Delmondes; Ribeiro, Felipe Barbosa; Siqueira, Jefferson Costa de; Lanna, Eduardo Arruda Teixeira; Takishita, Sylvia Sanae; Souza, Thalles José Rego de; Porto, Neliane Galvão (Semina: Ciências Agrárias, 2018)
The objective of this study was to determine the optimal digestible threonine to lysine ratios in diets of tambaqui (Colossoma macropomum) juveniles. Five-hundred fish with a mean Â± SE initial weight of 2.16 Â± 0.03 g were used in a completely randomized design, consisting of four treatments, five replicates per treatment, and 25 fish per experimental unit. The treatments consisted of four isoenergetic, isophosphoric, isocalcic, and isolisinic (1.45%) diets, consisting of a basal diet supplemented with four L-threonine levels (1.013, 1.085, 1.158, and 1.230%), resulting in different threonine to lysine ratios (70, 75, 80, and 85%). Fish were maintained in twenty 500-L aquaria with independent water supply, drainage, and aeration systems, and were fed to apparent satiation six times a day for 45 days. Performance, feed efficiency, daily protein and fat deposition, body moisture content, and nitrogen retention efficiency of fish were evaluated. The digestible threonine intake increased linearly, and the efficiency of threonine for weight gain decreased quadratically, with increasing digestible threonine to lysine ratios. Weight gain, specific growth rate, feed:gain ratio, protein efficiency for weight gain, and nitrogen retention efficiency of fish increased in a quadratic manner with increasing digestible threonine to lysine ratios up to the levels of 75.96, 76.06, 76.36, 76.47, and 74.02%, respectively. It was concluded that the digestible threonine to lysine ratio for use in diets of juvenile tambaqui to achieve optimal performance and nitrogen retention efficiency is 76 and 74%, respectively, which corresponds to a digestible threonine level of 1.102 and 1.073%.